Ground-state configuration of neutron-rich Aluminum isotopes through Coulomb Breakup - Chakraborty S. (EPJ Web of Conferences, 2014)
Neutron-rich 34,35Al isotopes have been studied through Coulomb excitation using LAND-FRS setup at GSI, Darmstadt. The method of invariant mass analysis has been used to reconstruct the excitation energy of the nucleus prior to decay. Comparison of experimental CD cross-section with direct breakup model calculation with neutron in p3/2 orbital favours 34Al(g.s)⊗νp3/2 as ground state configuration of 35Al. But ground state configuration of 34Al is complicated as evident from γ-ray spectra of 33Al after Coulomb breakup of 34Al.